1971
DOI: 10.1177/001440297103700604
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nonprofessional Persons in Teaching Language Skills to Mentally Retarded Children

Abstract: This study reviews a 2 year research project in which two former psychiatric aides were trained to serve as language developmentalists for small groups of institutionalized severely retarded children. Forty children participating in the program were compared with a matched control group on variables of IQ, language age, and social quotient. Children attending language classes met daily for approximately one hour. They were taught from the Peabody Language Development Kits and a series of lessons developed duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1972
1972
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…When sessions were conducted, the residents were often reinforced for maladaptive behavior and not reinforced for adaptive behavior. Despite the inconsistency of application, the use of direct-care staff or other nonprofessionals to carry out or maintain treatment programs in institutional settings is probably necessary if the program is to succeed (Guess, Rutherford, Smith, & Ensminger, 1970; adaptive behavior (around 15 %) and increase in maladaptive behavior (around 10%) was not severe. The real gains are apparent when the follow-up data are compared to the original baselines in the austere condition.…”
Section: Phase Comparisonsmentioning
confidence: 99%
“…When sessions were conducted, the residents were often reinforced for maladaptive behavior and not reinforced for adaptive behavior. Despite the inconsistency of application, the use of direct-care staff or other nonprofessionals to carry out or maintain treatment programs in institutional settings is probably necessary if the program is to succeed (Guess, Rutherford, Smith, & Ensminger, 1970; adaptive behavior (around 15 %) and increase in maladaptive behavior (around 10%) was not severe. The real gains are apparent when the follow-up data are compared to the original baselines in the austere condition.…”
Section: Phase Comparisonsmentioning
confidence: 99%
“…A paucity of research exists with respect to treatment options for communicative impairments in individuals with mental retardation (Guess, Smith, & Ensminger, 1971;Storey et al, 1995;Warren & Yoder, 1997), with the majority of the research attention devoted to children. Storey et al (1995) identified 19 studies examining communication intervention strategies for adults in supported employment.…”
mentioning
confidence: 99%
“…The number of training and credentialing models has also demonstrated commensurate growth (Pickett, 1979). Paraprofessionals have been used successfully across exceptionalities (Budner, Arnold, & Goodman, 1971;Cowan, Dorr, Sandler, & McWilliams, 1971;Frith, Lindsey, & Edwards, in press;Guess, Smith, & Ensminger, 1971;Palmer, 1975;Schortinghaus & Frohman, 1974) and in a variety of educational and community settings (Bayes & Neiii, 1978;Bireribaum & Ahmed, 1978;Frith & Lindsey, 1980). However, the literature contains relatively little information that describes the use-of paraprofessionals within the special needs program of vocational education (cf., Arkansas Department of Education, 1975;Dean, 1977).…”
Section: Greg Frith: Paraprofessionals In the Vocational Special Needmentioning
confidence: 99%